TEACHING ENGLISH LANGUAGE IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CONTEXTS: A REVIEW STUDY - Sahar Sabbar Zamil (Perkumpulan Madani Publisher Indonesia, 2025)
This review study examines the teaching of English language in English as a Foreign Language (EFL) context. Its main purpose is to explore the major teaching methods, approaches, and practices commonly used in EFL classrooms, with particular attention to the development of the four language skills: listening, speaking, reading, and writing. The study also discusses the roles of teachers and learners, as well as challenges faced by EFL instructors, such as limited exposure to authentic language and large class sizes. By reviewing both theoretical frameworks and previous empirical studies, the article identifies effective strategies for enhancing learners’ language proficiency. Findings indicate that communicative and learner-centered approaches are generally more successful than traditional methods. The study concludes with practical recommendations for EFL teachers and suggests directions for future research in the field of English language teaching.